Implementasi Client-Server Pada Sistem Informasi Pengolahan Nilai Siswa Menggunakan Object-Oriented Programming - Wahyuni, Ullya Mega; Fitrilina, Fitrilina (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2020)
ABSTRACTThe use of information technology in educational institutions be necessary for work to be efficient and flexible. The process of reporting student data and assessment results at SMA Negeri 1 Dharmasraya is still manual using paper (paper-based), and there is no specific storage for the database. To make reports on student learning outcomes and share resources easier then an information system was built on a client-server network using object-oriented programming with a centralized database so that the stored data can be organized. The build systems using the System Development Life Cycle waterfall model, which starts from the analysis, design, coding, testing, and maintenance. The results of this study are the establishment of a multiuser system that implements the use of client-server computer networks to process student grades.Key Words: Client-Server, Information Systems, OOP